1976
DOI: 10.1172/jci108588
|View full text |Cite
|
Sign up to set email alerts
|

Bone resorption in organ culture: inhibition by the divalent cation ionophores A23187 and X-537A.

Abstract: The ionophores A23187 and X-537A were used as probes to investigate the possible role of calcium uptake by bone as a mediator for the stimulation of bone resorption induced by parathyroid hormone (PTH) and other agents in cultured mouse calvaria. The ionophores alone at concentrations from 1 nM to 20 ,uM did not stimulate bone resorption, nor did they potentiate bone resorption stimulated by submaximal concentrations of PTH after either brief (15-60 min) or extended (1-3 day) exposure to the ionophores. Unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

1978
1978
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 29 publications
0
22
2
Order By: Relevance
“…However, they were unable to demonstrate any effect of DPH on cAMP generation. The basis for the divergence of these results from the findings of the present studies is unclear, but could be the result of species differences, recently demonstrated differences in the responsitivity of calvaria and long bones to certain resorptive stimuli (27), or merely to differences in the concentrations of drug employed.…”
Section: Effects Of Diphenylhydantoin and Phenobarbital On Bone Resorcontrasting
confidence: 89%
“…However, they were unable to demonstrate any effect of DPH on cAMP generation. The basis for the divergence of these results from the findings of the present studies is unclear, but could be the result of species differences, recently demonstrated differences in the responsitivity of calvaria and long bones to certain resorptive stimuli (27), or merely to differences in the concentrations of drug employed.…”
Section: Effects Of Diphenylhydantoin and Phenobarbital On Bone Resorcontrasting
confidence: 89%
“…However, in the absence of more direct assays of src activity, the possibility ofother intracellular TKs mediating 160-140-0 = 120-11 10 9 -LOG [PTHJ osteoblasts. Others and we have shown that the pleiotropic functions of these hormones on bone metabolism can be explained on the basis of antagonistic effects between the Ca2+ and cAMP signaling pathways (41)(42)(43)(44)56). With respect to cell growth, the cAMP messenger system is antiproliferative, while…”
Section: Methodsmentioning
confidence: 99%
“…It is now well established that the osteoblast plays a key role in both bone formation and bone resorption processes stimulated by osteotropic agents (39,40). Moreover, the Ca2' and cAMP messenger systems generated inside the osteoblastic cytosol mediate many of the effects of calciotropic hormones (41)(42)(43)(44). Given the in vivo observation of cooperativity between IL-6 and calciotropic hormones on bone remodeling, it is conceivable that the cytokine impinges on transduction pathways generated by hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal mouse calvaria were placed in organ culture as free-floating bones as described (16)(17)(18). The medium was Dulbecco's modified Eagle's medium supplemented with heat-inactivated (60°C for 1 hr) horse serum (final concentration, 15%).…”
Section: Methodsmentioning
confidence: 99%
“…Medium was changed at this time, and fresh control medium or medium containing specific treatments was added. Bone resorption was determined by measuring the release of calcium (40Ca2+) from the calvaria into the medium at 48 hr after addition of bone resorptionstimulating factors or drugs (16,17).…”
Section: Methodsmentioning
confidence: 99%